(untitled) (Research, Society and Development, 2020)
Currently, autism is classified as an invasive development disorder that involves serious lifelong difficulties in social and communicative skills - in addition to those attributed to overall developmental delay - as well as limited and repetitive behaviors and interests. Autism children are very selective and persistent to the new, making it difficult to insert new experiences with food. The objective of this study is to investigate in the literature the nursing team’s performance in face of the autistic child’s food selectivity. It is a literature review. The alimentary selectivity (SA) is characterized by the junction of alimentary behaviors, such as: refusal to eat, difficulties in consuming new foods and a reduced intake of varieties. The connection between the nurse, the autistic person and his relatives becomes of fundamental importance, since in the performance of the nursing’s work a careful look is shown, devoid of prejudices, attentive to the needs of the other and his suffering, since most of the times there will be the difficulty of oral expression on the part of the autistic, being the nurse responsible for listening and providing differentiated assistance.